Sistem Pembuktian terhadap Perceraian di Indonesia - Yuni Priskila Ginting; Axel Imanuel Tania; Cherish Young; Felicia Evelyn; Jennifer Almelia Lim; Kenzie Betha Addison; Suhan Chae; Thalia Jamiana Kuang (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The legal evidentiary system in divorce cases in Indonesia is an important aspect of family law that has an influence on the outcome of a marriage break-up. Divorce, as a legal act, is the official termination of the marriage bond between husband and wife that is recognized by a court decision. Filing for a divorce process can only be done before a Court Hearing; this happens if previous mediation efforts have been made by the competent Court but have not yielded results. In the context of civil law, a divorce application by a husband and wife can only be accepted based on clear reasons and regulated by law. Divorce is the last option in resolving conflicts between husband and wife after various efforts to maintain the marital relationship have been made but have not produced the expected changes and indicate that the husband and wife are no longer able to live together as a married couple. To better understand the legal regulations regarding divorce in the Indonesian legal system, this journal article discusses the legal evidentiary system for this matter.